A method for preparing CuCrNb material for high voltage level

Through the specific ratio and process of Cu powder, Cr powder and Nb powder, high voltage grade CuCrNb materials were prepared, which solved the brittleness and conductive rod deformation of alloy materials, improved the conductivity and strength, and extended the vacuum arc extinguishing chamber service life.

CN117816952BActive Publication Date: 2024-12-24SHAANXI SIRUI ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311815731.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2024-12-24
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

The existing CuCrNb alloy materials exhibit brittleness problems at high temperatures, which affects its engineering application. In addition, the traditional vacuum arc extinguishing chamber conductive rods are prone to deform and bend when used at high frequency, resulting in shortening of equipment life and frequent failures.

Method used

Cu powder, Cr powder, and Nb powder are prepared according to the atomic mass ratio, and are subjected to cold isostatic pressure, vacuum sintering, vacuum consumable arc smelting, hot forging, annealing, solid solution and aging treatment, combined with electrical pulse treatment and spraying agent instantaneously Temperature change technology prepares CuCrNb materials with high voltage grade.

Benefits of technology

It significantly improves the conductivity and strength of CuCrNb material, extends the service life of the vacuum arc extinguishing chamber, and enhances the safety and reliability of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117816952B_ABST
    Figure CN117816952B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a CuCrNb material for high voltage level, including S1 powder mixing, S2 cold isostatic pressing, S3 vacuum sintering, S4 vacuum consumable arc melting, S5 hot forging deformation, S6 annealing, S7 solution treatment, S8 aging treatment, and S9 machining. The present invention realizes the preparation of CuCrNb material for high voltage level, and provides a conductive rod material with better performance for vacuum interrupter, thereby greatly improving the service life of vacuum interrupter and improving the safety of vacuum interrupter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper alloy materials, and in particular to a method for preparing a CuCrNb material for high voltage level. Background Art

[0002] The electrical conductivity and strength of copper alloys are two contradictory properties. When designing copper alloys, it is necessary to improve the strength of copper alloys while ensuring their high electrical conductivity. According to alloying theory, as the degree of alloying increases, the strength of the alloy can be significantly improved, but it will also have an adverse effect on its electrical conductivity. Therefore, when selecting alloying elements, the effects of both strength and electrical conductivity must be considered comprehensively. The effect of strengthening copper alloys by alloying mainly depends on the following two aspects: on the one hand, the strengthening effect of alloying elements depends on the curve of their solid solubility changing with temperature; on the other hand, the morphology, size, distribution and other characteristics of the second phase particles play a decisive role in the strengthening effect of the alloy.

[0003] As a kind of intermetallic compound, Laves phase Cr2Nb not only has high hardness and high melting point, but also has very good high-temperature oxidation resistance, room temperature and high-temperature strength, very high creep resistance and excellent hot corrosion resistance. It is regarded as a very potential high-temperature structural material. Its use temperature is expected to exceed 1200℃, which can meet the development requirements of high-temperature alloys. However, the room temperature brittleness of the alloy is relatively large, which greatly limits the engineering application of the alloy. The large room temperature brittleness of Cr2Nb is related to the crystal structure of the phase. The symmetry of the Cr2Nb unit cell is poor, and the slip system of the unit cell is less during deformation, resulting in the large room temperature brittleness of the alloy. Therefore, further improving the room temperature brittleness of Cr2Nb and giving full play to the excellent high temperature performance of Cr2Nb have become the key factors for the development of this alloy.

[0004] Patent CN110512114A discloses a method for preparing a CuCr contact material containing a Cr2Nb phase. The raw materials are mixed in proportion, and the prepared raw materials are placed in a ceramic crucible. Under vacuum conditions, the raw materials are melted by gradient heating. When the raw materials are completely melted, the composition is uniformed under the action of electromagnetic stirring, and the melt in the ceramic crucible is poured into a water-cooled mold, cooled out of the furnace, and the ingot is deformed to the required size by a hot forging process, followed by heat treatment. This method uses a vacuum induction melting method, which is affected by the cooling rate to prepare a coarse and uneven Cr2Nb phase structure, which affects the strength, hardness, and high temperature resistance of CuCrNb.

[0005] Patent CN111440963A discloses a high heat-resistant and high-conductivity CuCrNb copper alloy and a preparation method thereof. The composition, by weight percentage, is: Cr 2.0-10.0%, Nb 1.0-5.0%, Co 0.05-0.5%, Mg 0.05-0.2%; the rest is Cu and inevitable impurities. The raw materials are melted, powdered by inert gas atomization method, sintered by SPS in a reducing atmosphere, hot rolled or hot extruded, then cold rolled or cold drawn, and finally annealed and passivated to obtain a high heat-resistant and high-conductivity CuCrNb copper alloy. The Cr2Nb phase of CuCrNb prepared by this method is unstable and not easy to mass produce.

[0006] The vacuum interrupter is mainly composed of an airtight insulation system, a conductive system, a shielding system, and a contact system. The conductive system mainly conducts current, including dynamic and static conductive rods. At present, the conductive rods are made of oxygen-free copper, but the conventional oxygen-free copper rods for vacuum interrupters will deform, stagnate, and bend when used at a high frequency, which greatly reduces the service life of the vacuum interrupter and causes serious failures, resulting in the inability to quickly, reliably, and safely cut off the power supply. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a method for preparing CuCrNb material for high voltage level.

[0008] The technical solution of the present invention is: a method for preparing a CuCrNb material for high voltage level, comprising the following steps:

[0009] S1, Mixed powder

[0010] Cu powder, Cr powder and Nb powder are mixed according to the atomic mass ratio, Cr: 1.5-4%, Nb: 0.75-2%, Cu as the balance, stainless steel balls are added, and mixed powder is obtained after ball milling;

[0011] S2, cold isostatic pressing

[0012] The mixed powder is put into the rubber sleeve, and the rubber sleeve is fixed to the steel jacket. The pressure of the cold isostatic press is 220-280Mpa, and the pressure is maintained for 5-10 minutes to obtain the electrode rod;

[0013] S3, vacuum sintering

[0014] The electrode rod is placed in a graphite card slot, and then placed in a vacuum sintering furnace for vacuum sintering to obtain a vacuum sintered electrode rod;

[0015] S4. Vacuum consumable arc melting

[0016] Put the vacuum sintered electrode rod into the vacuum consumable arc furnace for melting, turn on the refrigerator, close the furnace door and evacuate to 5*10-3 mbar, fill with inert He gas 80-150mbar for atmosphere protection, and cool in the mold after smelting to obtain an ingot;

[0017] S5. Hot forging deformation

[0018] The ingot is forged and deformed to the required size by hot forging process, the hot forging temperature is controlled at 700-980℃, and the temperature is kept for 1-3h;

[0019] S6, Annealing

[0020] The forged ingot is placed in an annealing furnace for annealing, the temperature is controlled at 400-750°C, and the temperature is kept for 1-4 hours to obtain the annealed forged ingot;

[0021] S7, solution treatment

[0022] The annealed forged ingot is placed in a muffle furnace and heated to 850-960°C at room temperature for 1-2 hours, kept at 850-960°C for 1-2 hours, and then taken out of the furnace and cooled to obtain a solution treated forged ingot;

[0023] S8. Aging treatment

[0024] The forged ingot after the solution treatment is heated to 600°C at room temperature in a chamber furnace for 1 hour, kept at 600°C for 4-8 hours, air-cooled after being taken out of the furnace, and naturally cooled to obtain the forged ingot after aging treatment;

[0025] S9, Machining

[0026] The aged forged ingot is processed into the required shape according to the drawing using machining equipment.

[0027] Furthermore, in S1, the Cu powder is electrolytic Cu powder with a mesh size of less than 200, the Cr powder is 300-400 mesh Cr powder obtained by aluminotherm reduction, and the Nb powder is 200-325 mesh Nb powder obtained by aluminotherm reduction.

[0028] Note: The use of Cu powder, Cr powder and Nb powder with the above mesh size can meet the powder mesh size requirements of cold isostatic pressing and powder sintering, and can prepare CuCrNb materials with performance parameters that meet production requirements.

[0029] Furthermore, in S1, the ball milling time of the ball milling treatment is 300-500 r / min, and the ball mill mixer rotates 360 degrees for 4-8 hours to perform sufficient mixing.

[0030] Note: By ball milling the mixed powder with the above-mentioned ball milling parameters, the mixing uniformity of the mixed powder can be improved, and the shape of the powder can be improved, thereby increasing the density of the electrode rod pressed by cold isostatic pressing, and further improving the performance parameters of the subsequent preparation of CuCrNb materials.

[0031] Furthermore, in S2, the rubber sleeve is Φ90mm-Φ95mm*1100mm; the length of the electrode rod is 600-800mm, and the diameter is 65-80mm.

[0032] Note: The above-mentioned rubber sleeve size can be used to prepare electrode rods of required specifications and sizes as required. The above-mentioned electrode rods with a length of 600-800 mm and a diameter of 65-80 mm are the specifications and sizes required for production, but are not limited to this specification and size. Electrode rods of other specifications and sizes can be cold isostatically pressed as required.

[0033] Furthermore, in S3, the vacuum sintering is specifically as follows: vacuuming for 1.5-3h, and the vacuum reaches 5*10 -3 The pa vacuum sintering furnace is automatically heated, and the heating temperature is 1100-1200℃ for sintering for 28-32h, and the temperature is kept for 4-6h. When the temperature drops to 700-800℃, Ar gas is filled and the fan is turned on for rapid cooling. When the temperature drops below 80℃, the fan is turned off and the furnace is taken out to obtain the electrode rod after vacuum sintering.

[0034] Note: Using the above vacuum sintering parameters to perform vacuum sintering of the electrode rod can effectively remove gas and impurities in the electrode rod, improve the purity of the CuCrNb material, and better control the composition and structure of the CuCrNb material, thereby improving the performance of the CuCrNb material.

[0035] Furthermore, in S4, the cooling water pressure of the refrigerator is 3-5 bar, the compressed air is 6-8 bar, the He pressure is ≥2 bar, and the inlet water temperature is 16-24°C; the smelting current of the smelting is 2-5KA, the smelting voltage is 15-30V, and the droplet rate is 0.3-2 / s; the cooling water flow rate of the cooling is 200-300L / min, and the ingot is obtained after cooling for 10-20 minutes.

[0036] Note: By adopting the above vacuum consumable arc melting parameters for ingot production, the gas and impurities in the CuCrNb material can be further removed in a vacuum environment, the output precision of the CuCrNb material can be improved, and the melting can be carried out under the current and voltage of the above parameters by precise control to ensure the stability and controllability of the melting process. Moreover, the above vacuum consumable arc melting parameters can meet the ingot production requirements while greatly shortening the production cycle.

[0037] Furthermore, in S7, the temperature is kept at 850-960° C. for 1-2 hours, and the ingot is taken out of the furnace and subjected to water quenching to obtain a solution treated forged ingot.

[0038] Description: Water quenching during solution treatment can wash away the high temperature of the ingot surface, achieve the purpose of rapid cooling, prevent the growth of metal grains, and ensure the refinement of the structure after solution treatment. During the rapid cooling process of water quenching, the internal structure of the CuCrNb material can become dense and the grain size can be reduced, thereby improving the strength and hardness, and eliminating stress concentration and uneven deformation, thereby improving the performance of the CuCrNb material.

[0039] Furthermore, in S7, the temperature is kept at 850-960°C for 1-2 hours, the frequency of the forging ingot is 220 Hz, and the current density is 380-450 A / mm 2 , electric pulse treatment with a power-on time of 750 to 900 ms,

[0040] During the electric pulse treatment, the forged ingot is sprayed once and then buried in low-temperature quartz powder.

[0041] When the temperature sensor detects that the temperature of the forging ingot drops to 500℃±10℃, 300℃±10℃, and 100℃±10℃, the bin containing the low-temperature quartz powder is automatically lowered, and the forging ingot is sprayed twice, three times, and four times in sequence;

[0042] The spraying temperature and concentration of the spraying agent used in the first, second, third, and fourth spraying treatments were gradually increased, and the spraying dosage of the first, second, third, and fourth spraying treatments was 10 mL / cm 2 , the spraying time is 400-500ms.

[0043] Description: The above-mentioned electric pulse treatment can strengthen and change the microstructure and mechanical properties of CuCrNb materials through thermal and non-thermal effects in a short time. The above treatment method is mainly divided into two stages;

[0044] The first stage is the combined action of electric pulse treatment and one-time spraying treatment. This treatment can significantly improve the electrical conductivity of CuCrNb materials. Through the time difference between spraying time and electric pulse power-on time, this link has a combined action stage of electric pulse treatment and one-time spraying treatment and a single action stage of electric pulse treatment. Such stage control can make the one-time spraying agent play a good role and improve the treatment strengthening effect of the first stage.

[0045] The second stage is spraying controlled at temperature nodes of 500℃±10℃, 300℃±10℃, and 100℃±10℃. Spraying agents with different concentrations and spraying temperatures are used in turn to carry out treatment, so that the CuCrNb material can be temperature-controlled at the above-mentioned temperature nodes, which is more conducive to the refinement of the structure after solution treatment, thereby further improving the performance of the CuCrNb material.

[0046] Furthermore, the temperature of the low-temperature quartz powder is 10-20° C., and the low-temperature quartz powder is continuously stirred by a stirrer; the operating environment temperature is room temperature;

[0047] The temperature of the spraying agent for the first spraying treatment is 70-80°C, and the concentration of the spraying agent is 75-78%; the temperature of the spraying agent for the second spraying treatment is 40-50°C, and the concentration of the spraying agent is 50-65%; the temperature of the spraying agent for the third spraying treatment is 30-35°C, and the concentration of the spraying agent is 30-40%; the temperature of the spraying agent for the fourth spraying treatment is 20-25°C, and the concentration of the spraying agent is 20-30%.

[0048] Note: By using the above-mentioned spraying agents with different concentrations and spraying temperatures for treatment, the CuCrNb material can be instantaneously changed in temperature at each temperature node. Through our tests, we found that under such instantaneous temperature change treatment, it is more conducive to the refinement of the structure of the CuCrNb material and can further improve the performance of the CuCrNb material.

[0049] Furthermore, the spray is formed by mixing water and reagents, the concentration of the spray refers to the volume ratio of the reagent to water, the reagent for the first spray treatment is formed by mixing 20-25 g / L of copper sulfate, 3-8 g / L of sodium tartrate and water, the reagent for the second, third and fourth spray treatments is formed by mixing 20-25 g / L of benzotriazole, 30-50 g / L of hydroxymethyl cellulose and water, and the spray should be prepared and used immediately.

[0050] Note: By using the reagents for the above-mentioned single spraying treatment in the first stage, the treatment effect of the first stage can be effectively improved in conjunction with the electric pulse treatment, thereby improving the performance of the CuCrNb material; by using the reagents for the above-mentioned secondary, tertiary, and quadruple spraying treatments in the second stage, the instantaneous temperature change can be carried out in conjunction with the above-mentioned treatment process, thereby further improving the performance of the CuCrNb material.

[0051] The beneficial effects of the present invention are:

[0052] The present invention adopts Cu powder, Cr powder and Nb powder as raw materials to manufacture CuCrNb material by vacuum consumable arc melting, and performs solid solution aging treatment to prepare CuCrNb material for high voltage level, and significantly improves the strength of the CuCrNb material while ensuring the conductivity of the CuCrNb material, so that the CuCrNb material has high conductivity and high strength, thereby providing a conductive rod material with better performance for the vacuum interrupter, thereby greatly improving the service life of the vacuum interrupter and improving the safety of the vacuum interrupter. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1It is a 500X scanning electron microscope of the CuCr2Nb1 material of the present invention.

[0054] Figure 2 It is a 1000X scanning electron microscope of the CuCr4Nb2 material of the present invention. DETAILED DESCRIPTION

[0055] The present invention is further described in detail below in conjunction with specific implementation methods to better reflect the advantages of the present invention.

[0056] Embodiment 1:

[0057] A method for preparing a CuCrNb material for high voltage level comprises the following steps:

[0058] S1, Mixed powder

[0059] Cu powder is electrolytic Cu powder with mesh size less than 200, Cr powder is 300-400 mesh Cr powder reduced by aluminothermically, and Nb powder is 200-325 mesh Nb powder reduced by aluminothermically. Cu powder, Cr powder and Nb powder are mixed according to the atomic mass ratio, Cr: 2%, Nb: 1%, and Cu as the balance. Stainless steel balls are added. The ball milling time is 420 r / min. The ball mill mixer rotates 360 degrees for full mixing for 7 hours. After ball milling, mixed powder is obtained.

[0060] S2, cold isostatic pressing

[0061] The mixed powder is put into a rubber sleeve with a diameter of 90 mm; the rubber sleeve is fixed to the steel jacket, and the pressure of the cold isostatic press is 260 MPa, and the pressure is maintained for 7 minutes to obtain an electrode rod with a length of 700 mm and a diameter of 70 mm;

[0062] S3, vacuum sintering

[0063] The electrode rod is placed in the graphite card slot, and then placed in the vacuum sintering furnace. The vacuum is evacuated for 2.5 hours until the vacuum reaches 5*10 -3 The pa vacuum sintering furnace is automatically heated, and the heating temperature is 1180℃ for sintering for 30 hours, and the temperature is kept for 5 hours. When the temperature drops to 760℃, Ar gas is filled, and the fan is turned on to quickly cool down. When the temperature drops below 80℃, the fan is turned off and the furnace is taken out to obtain the electrode rod after vacuum sintering;

[0064] S4. Vacuum consumable arc melting

[0065] Put the vacuum sintered electrode rod into the vacuum consumable arc furnace for melting, turn on the refrigerator, close the furnace door and evacuate to 4.9*10 -3 mbar, fill with inert He gas 120mbar for atmosphere protection, and cool in the mold after smelting to obtain an ingot;

[0066] The cooling water pressure of the refrigerator is 4 bar, the compressed air is 7 bar, the He pressure is 2 bar, and the water inlet temperature is 21°C; the smelting current is 4KA, the smelting voltage is 25V, and the droplet rate is 1.5 / s; the cooling water flow rate of the cooling is 260L / min, and the ingot is obtained after cooling for 15 minutes.

[0067] S5. Hot forging deformation

[0068] The ingot is forged and deformed to the required size by hot forging process. The hot forging temperature is controlled at 950℃ and kept warm for 2.5 hours to ensure that the ingot is thoroughly burned through and prevent cracks from appearing during forging.

[0069] S6, Annealing

[0070] The forged ingot is placed in an annealing furnace for annealing, the temperature is controlled at 630°C, and the temperature is kept for 3 hours to obtain the annealed forged ingot;

[0071] S7, solution treatment

[0072] The annealed forged ingot is placed in a muffle furnace and heated to 920°C at room temperature for 1.5 hours, kept at 920°C for 1.5 hours, and then taken out of the furnace and water quenched to obtain a solution treated forged ingot;

[0073] S8. Aging treatment

[0074] The forged ingot after the solution treatment is heated to 600°C at room temperature in a chamber furnace for 1 hour, kept at 600°C for 6 hours, air-cooled after being taken out of the furnace, and naturally cooled to obtain the forged ingot after aging treatment;

[0075] S9, Machining

[0076] The aged forged ingot is processed into the required shape according to the drawing using machining equipment.

[0077] Embodiment 2:

[0078] A method for preparing a CuCrNb material for high voltage level comprises the following steps:

[0079] S1, Mixed powder

[0080] Cu powder is electrolytic Cu powder with mesh size less than 200, Cr powder is 300-400 mesh Cr powder obtained by aluminotherm reduction, and Nb powder is 200-325 mesh Nb powder obtained by aluminotherm reduction. Cu powder, Cr powder and Nb powder are mixed according to the atomic mass ratio, Cr: 1.5%, Nb: 0.75%, and Cu as the balance. Stainless steel balls are added. The ball milling time is 300 r / min. The ball mill mixer is rotated 360 degrees for full mixing for 4 hours. After ball milling, mixed powder is obtained.

[0081] S2, cold isostatic pressing

[0082] The mixed powder is put into a rubber sleeve with a diameter of 90 mm; the rubber sleeve is fixed to the steel jacket, and the pressure of the cold isostatic press is 220 MPa, and the pressure is maintained for 5 minutes to obtain an electrode rod with a length of 700 mm and a diameter of 70 mm;

[0083] S3, vacuum sintering

[0084] The electrode rod is placed in the graphite card slot, and then placed in the vacuum sintering furnace. The vacuum is evacuated for 1.5 hours until the vacuum reaches 5*10 -3 The pa vacuum sintering furnace is automatically heated, and the heating temperature is 1100℃ for sintering for 28h, and the temperature is kept for 4h. When the temperature drops to 700℃, Ar gas is filled, and the fan is turned on to quickly cool down. When the temperature drops below 80℃, the fan is turned off and the furnace is taken out to obtain the electrode rod after vacuum sintering;

[0085] S4. Vacuum consumable arc melting

[0086] Put the vacuum sintered electrode rod into the vacuum consumable arc furnace for melting, turn on the refrigerator, close the furnace door and evacuate to 4.9*10 -3 mbar, fill with inert He gas 80mbar for atmosphere protection, and cool in the mold after smelting to obtain an ingot;

[0087] The cooling water pressure of the refrigerator is 3 bar, the compressed air is 6 bar, the He pressure is 2 bar, and the water inlet temperature is 16°C; the smelting current is 2KA, the smelting voltage is 15V, and the droplet rate is 0.3 / s; the cooling water flow rate of the cooling is 200L / min, and the ingot is obtained after cooling for 10 minutes.

[0088] S5. Hot forging deformation

[0089] The ingot is forged and deformed to the required size by hot forging process. The hot forging temperature is controlled at 700℃ and kept warm for 1 hour to ensure that the ingot is thoroughly burned through to prevent cracks from appearing during forging.

[0090] S6, Annealing

[0091] The forged ingot is placed in an annealing furnace for annealing, the temperature is controlled at 400°C, and the temperature is kept for 1 hour to obtain the annealed forged ingot;

[0092] S7, solution treatment

[0093] The annealed forged ingot is placed in a muffle furnace and heated from room temperature to 850°C for 1 hour, and kept at 850°C for 1 hour. The forged ingot is taken out of the furnace and water quenched to obtain a solution treated forged ingot.

[0094] S8. Aging treatment

[0095] The forged ingot after the solution treatment is heated to 600°C at room temperature in a chamber furnace for 1 hour, kept at 600°C for 4 hours, air-cooled after being taken out of the furnace, and naturally cooled to obtain the forged ingot after aging treatment;

[0096] S9, Machining

[0097] The aged forged ingot is processed into the required shape according to the drawing using machining equipment.

[0098] Embodiment 3:

[0099] A method for preparing a CuCrNb material for high voltage level comprises the following steps:

[0100] S1, Mixed powder

[0101] Cu powder is electrolytic Cu powder with mesh size less than 200, Cr powder is 300-400 mesh Cr powder reduced by aluminothermically, and Nb powder is 200-325 mesh Nb powder reduced by aluminothermically. Cu powder, Cr powder and Nb powder are mixed according to the atomic mass ratio, Cr: 4%, Nb: 2%, and Cu as the balance. Stainless steel balls are added. The ball milling time is 500r / min. The ball mill mixer rotates 360 degrees for full mixing for 8h. After ball milling, mixed powder is obtained.

[0102] S2, cold isostatic pressing

[0103] The mixed powder is put into a rubber sleeve with a diameter of 90 mm; the rubber sleeve is fixed to the steel jacket, and the pressure of the cold isostatic press is 280 MPa, and the pressure is maintained for 10 minutes to obtain an electrode rod with a length of 700 mm and a diameter of 70 mm;

[0104] S3, vacuum sintering

[0105] The electrode rod is placed in the graphite card slot, and then placed in the vacuum sintering furnace. The vacuum is evacuated for 3 hours until the vacuum reaches 5*10 -3 The pa vacuum sintering furnace is automatically heated, and the heating temperature is 1200℃ for sintering for 32 hours, and the temperature is kept for 6 hours. When the temperature drops to 800℃, Ar gas is filled, and the fan is turned on to quickly cool down. When the temperature drops below 80℃, the fan is turned off and the furnace is taken out to obtain the electrode rod after vacuum sintering;

[0106] S4. Vacuum consumable arc melting

[0107] Put the vacuum sintered electrode rod into the vacuum consumable arc furnace for melting, turn on the refrigerator, close the furnace door and evacuate to 4.9*10 -3 mbar, fill with inert He gas 150mbar for atmosphere protection, and cool in the mold after smelting to obtain an ingot;

[0108] The cooling water pressure of the refrigerator is 5 bar, the compressed air is 8 bar, the He pressure is 2 bar, and the water inlet temperature is 24°C; the smelting current is 5KA, the smelting voltage is 30V, and the droplet rate is 2 / s; the cooling water flow rate of the cooling is 300L / min, and the ingot is obtained after cooling for 20 minutes.

[0109] S5. Hot forging deformation

[0110] The ingot is forged and deformed to the required size by hot forging process. The hot forging temperature is controlled at 980℃ and kept warm for 3 hours to ensure that the ingot is thoroughly burned through and prevent cracks from appearing during forging.

[0111] S6, Annealing

[0112] The forged ingot is placed in an annealing furnace for annealing, the temperature is controlled at 750°C, and the temperature is kept for 4 hours to obtain the annealed forged ingot;

[0113] S7, solution treatment

[0114] The annealed forged ingot is placed in a muffle furnace and heated to 960°C at room temperature for 2 hours, and kept at 960°C for 2 hours. The forged ingot is taken out of the furnace and water quenched to obtain a solution treated forged ingot.

[0115] S8. Aging treatment

[0116] The forged ingot after the solution treatment is heated to 600°C at room temperature in a box furnace for 1 hour, kept at 600°C for 8 hours, air-cooled after being taken out of the furnace, and naturally cooled to obtain the forged ingot after aging treatment;

[0117] S9, Machining

[0118] The aged forged ingot is processed into the required shape according to the drawing using machining equipment.

[0119] In order to verify the CuCrNb material prepared in the above embodiment, the performance test of the CuCrNb material prepared in Examples 1-3 is now carried out, and the test results are shown in Table 1 below:

[0120] Table 1 Physical and chemical properties of CuCrNb materials

[0121]

[0122] It can be seen from the results in Table 1 above that the two main properties of copper alloy, conductivity and strength, have contradictory characteristics. Under the premise of improving conductivity, its hardness will decrease to a certain extent. Therefore, it is necessary to adjust the content of each component of CuCrNb material. Among them, the conductivity and hardness of Example 1 are relatively balanced, but it can also be selected as needed according to actual use requirements.

[0123] At the same time, in order to observe the organizational morphology of CuCrNb materials, the CuCr2Nb1 materials and CuCr4Nb2 materials are scanned by electron microscope. Figure 1 It is a 500X scanning electron microscope of CuCr2Nb1 material; Figure 2 This is a 1000X scanning electron microscope of CuCr4Nb2 material. It can be seen that the CuCr2Nb1 material and CuCr4Nb2 material have uniform tissues.

[0124] Embodiment 4:

[0125] The difference between this embodiment and embodiment 1 is that in S7, the temperature is kept at 920°C for 1.5 hours, the frequency of the forging ingot is 220Hz, and the current density is 430A / mm 2 , the electric pulse treatment with a power-on time of 870ms, during which the forging ingot is sprayed once, and then the forging ingot is buried in low-temperature quartz powder, and when the temperature sensor detects that the forging ingot has cooled to 500℃, 300℃, and 100℃, the bin containing the low-temperature quartz powder is automatically lowered, and the forging ingot is sprayed twice, three times, and four times in sequence;

[0126] It is understandable that the bin is equipped with a commercially available lifting motor and a temperature sensor, and is connected to a commercially available PLC controller to control the lifting of the lifting motor, and is also equipped with a commercially available nozzle and a liquid pump to achieve timed spraying;

[0127] Wherein, the temperature of the low-temperature quartz powder is 18°C, and the low-temperature quartz powder is continuously stirred by a stirrer; the operating environment temperature is room temperature; the temperature of the spraying agent for the first spraying treatment is 75°C, and the concentration of the spraying agent is 76%; the temperature of the spraying agent for the second spraying treatment is 45°C, and the concentration of the spraying agent is 62%; the temperature of the spraying agent for the third spraying treatment is 33°C, and the concentration of the spraying agent is 45%; the temperature of the spraying agent for the fourth spraying treatment is 23°C, and the concentration of the spraying agent is 27%;

[0128] The spraying temperature and concentration of the spraying agent used in the first, second, third, and fourth spraying treatments were gradually increased, and the spraying dosage of the first, second, third, and fourth spraying treatments was 10 mL / cm 2 , spraying time is 470ms;

[0129] The spray is formed by mixing water and reagents. The concentration of the spray refers to the volume ratio of the reagent to water. The reagent for the first spray treatment is formed by mixing 23g / L of copper sulfate, 7g / L of sodium tartrate and water. The reagent for the second, third and fourth spray treatments is formed by mixing 23g / L of benzotriazole, 45g / L of hydroxymethyl cellulose and water. The spray should be prepared and used immediately.

[0130] Embodiment 5:

[0131] This embodiment is basically the same as embodiment 4, except that the frequency used for forging the ingot is 220 Hz and the current density is 380 A / mm 2 , electric pulse treatment with power-on time of 750ms.

[0132] Embodiment 6:

[0133] This embodiment is basically the same as embodiment 4, except that the frequency used for forging the ingot is 220 Hz and the current density is 450 A / mm 2 , electric pulse treatment with power-on time of 900ms.

[0134] Embodiment 7:

[0135] This embodiment is basically the same as embodiment 4, except that the spraying dosage for the first, second, third, and fourth spraying treatments is 10 mL / cm 2 , the spraying time is 400ms.

[0136] Embodiment 8:

[0137] This embodiment is basically the same as embodiment 4, except that the spraying dosage for the first, second, third, and fourth spraying treatments is 10 mL / cm 2 , the spraying time is 500ms.

[0138] Embodiment 9:

[0139] This embodiment is basically the same as Embodiment 4, except that the temperature of the low-temperature quartz powder is 10°C, and the low-temperature quartz powder is continuously stirred by a stirrer; the operating environment temperature is room temperature; the temperature of the spraying agent for the first spraying treatment is 70°C, and the concentration of the spraying agent is 75%; the temperature of the spraying agent for the second spraying treatment is 40°C, and the concentration of the spraying agent is 50%; the temperature of the spraying agent for the third spraying treatment is 30°C, and the concentration of the spraying agent is 30%; the temperature of the spraying agent for the fourth spraying treatment is 20°C, and the concentration of the spraying agent is 20%.

[0140] Embodiment 10:

[0141] This embodiment is basically the same as Embodiment 4, except that the temperature of the low-temperature quartz powder is 20°C, and the low-temperature quartz powder is continuously stirred by a stirrer; the operating environment temperature is room temperature; the temperature of the spraying agent for the first spraying treatment is 80°C, and the concentration of the spraying agent is 78%; the temperature of the spraying agent for the second spraying treatment is 50°C, and the concentration of the spraying agent is 65%; the temperature of the spraying agent for the third spraying treatment is 35°C, and the concentration of the spraying agent is 40%; the temperature of the spraying agent for the fourth spraying treatment is 25°C, and the concentration of the spraying agent is 30%.

[0142] Embodiment 11:

[0143] This embodiment is basically the same as embodiment 4, except that the spray is formed by mixing water and reagents, the spray concentration refers to the volume ratio of reagents to water, the reagent for the first spray treatment is formed by mixing 20 g / L of copper sulfate, 3 g / L of sodium tartrate and water, the reagent for the second, third and fourth spray treatments is formed by mixing 20 g / L of benzotriazole, 30 g / L of hydroxymethyl cellulose and water, and the spray should be prepared and used immediately.

[0144] Embodiment 12:

[0145] This embodiment is basically the same as embodiment 4, except that the spray is formed by mixing water and reagents, the spray concentration refers to the volume ratio of reagents to water, the reagent for the first spray treatment is formed by mixing 25 g / L of copper sulfate, 8 g / L of sodium tartrate and water, the reagent for the second, third and fourth spray treatments is formed by mixing 25 g / L of benzotriazole, 50 g / L of hydroxymethyl cellulose and water, and the spray should be prepared and used immediately.

[0146] In order to verify the CuCrNb materials prepared in the above examples, the performance of the CuCrNb materials prepared in Examples 1-3 is tested.

[0147] Comparison 1: basically the same as Example 4, but the spraying agent used was water, and the other parameters and steps remained unchanged;

[0148] Comparison 2: basically the same as Example 4, but without applying the electric pulse treatment and the one-time spraying treatment, and the other parameters and steps remain unchanged;

[0149] The test results are shown in Table 2 below:

[0150] Table 2 Physical and chemical properties of CuCrNb materials

[0151]

[0152] It is understandable that the contents of O and N components cannot be precisely controlled, and they are only controlled at the O and N contents close to those in Example 1. Therefore, at the same Cr and Nb contents, the contents of O and N components are not measured, and the differences in the contents of O and N components are ignored.

[0153] It can be seen from the results in Table 2 above that different process parameters have a certain influence on the physical and chemical properties of the prepared CuCrNb material. By comparing Example 4 with Example 1, it can be seen that the conductivity and hardness of the original CuCr2Nb1 material can be effectively improved by using electric pulse treatment and one, two, three, and four spraying treatments;

[0154] By comparing Example 5, Example 6, Comparison 2 with Example 4, it can be seen that when no electric pulse treatment is applied and different electric pulse treatment parameters are used, the conductivity and hardness of the prepared CuCr2Nb1 material are affected to a certain extent, among which the CuCr2Nb1 material prepared by the electric pulse treatment parameters of Example 4 has the best performance;

[0155] By comparing Example 7 and Example 8 with Example 4, it can be seen that different spraying times of the spraying agent determine the instantaneous temperature change time, which has a certain influence on the conductivity and hardness of the prepared CuCr2Nb1 material, but the influence is not significant. Among them, the CuCr2Nb1 material prepared with the spraying time of Example 4 has relatively better performance.

[0156] By comparing Example 9 and Example 10 with Example 4, it can be seen that different temperatures and spraying agent concentrations have a certain influence on the conductivity and hardness of the prepared CuCr2Nb1 material, among which the CuCr2Nb1 material prepared with the relevant parameters of Example 4 has the best performance;

[0157] By comparing Example 11, Example 12, Comparison 1 and Example 4, it can be seen that the use of different sprays has a certain influence on the conductivity and hardness of the prepared CuCr2Nb1 material, among which the CuCr2Nb1 material prepared with the spray ratio of Example 4 has the best performance.

Claims

1. A method for preparing CuCrNb material for high voltage level, characterized in that: The following steps are involved: S1, Mixed powder Cu powder, Cr powder and Nb powder are mixed according to the atomic mass ratio, Cr: 1.5-4%, Nb: 0.75-2%, Cu as the balance, stainless steel balls are added, and mixed powder is obtained after ball milling; S2, cold isostatic pressing The mixed powder is put into the rubber sleeve, and the rubber sleeve is fixed to the steel jacket. The pressure of the cold isostatic press is 220-280Mpa, and the pressure is maintained for 5-10 minutes to obtain the electrode rod; S3, vacuum sintering The electrode rod is placed in a graphite card slot, and then placed in a vacuum sintering furnace for vacuum sintering to obtain a vacuum sintered electrode rod; S4. Vacuum consumable arc melting Put the vacuum sintered electrode rod into the vacuum consumable arc furnace for melting, turn on the refrigerator, close the furnace door and evacuate to 5*10 -3 mbar, fill with inert He gas 80-150mbar for atmosphere protection, and cool in the mold after smelting to obtain an ingot; S5. Hot forging deformation The ingot is forged and deformed to the required size by hot forging process, the hot forging temperature is controlled at 700-980℃, and the temperature is kept for 1-3h; S6, Annealing The forged ingot is placed in an annealing furnace for annealing, the temperature is controlled at 400-750°C, and the temperature is kept for 1-4 hours to obtain the annealed forged ingot; S7, solution treatment The annealed forged ingot is placed in a muffle furnace and heated to 850-960°C at room temperature for 1-2 hours, kept at 850-960°C for 1-2 hours, and then taken out of the furnace and cooled to obtain a solution treated forged ingot; S8. Aging treatment The forged ingot after the solution treatment is heated to 600°C at room temperature in a chamber furnace for 1 hour, kept at 600°C for 4-8 hours, air-cooled after being taken out of the furnace, and naturally cooled to obtain the forged ingot after aging treatment; S9, Machining Use machining equipment to process the aged ingot into the required shape according to the drawing; In S7, the temperature is kept at 850-960°C for 1-2 hours, the frequency of the forging ingot is 220Hz, and the current density is 380-450A / mm 2 , electric pulse treatment with a power-on time of 750 to 900 ms, During the electric pulse treatment, the forged ingot is sprayed once and then buried in low-temperature quartz powder. When the temperature sensor detects that the temperature of the forging ingot drops to 500℃±10℃, 300℃±10℃, and 100℃±10℃, the bin containing the low-temperature quartz powder is automatically lowered, and the forging ingot is sprayed twice, three times, and four times in sequence; The temperature of the spraying agent for the first spraying treatment is 70-80°C, and the concentration of the spraying agent is 75-78%; the temperature of the spraying agent for the second spraying treatment is 40-50°C, and the concentration of the spraying agent is 50-65%; the temperature of the spraying agent for the third spraying treatment is 30-35°C, and the concentration of the spraying agent is 30-40%; the temperature of the spraying agent for the fourth spraying treatment is 20-25°C, and the concentration of the spraying agent is 20-30%, and the spraying dosage for the first, second, third, and fourth spraying treatments is 10mL / cm 2 , the spraying time is 400-500ms.

2. The method for preparing a high voltage grade CuCrNb material according to claim 1, characterized in that: In S1, the Cu powder is electrolytic Cu powder with a mesh size of less than 200, the Cr powder is 300-400 mesh Cr powder obtained by aluminothermic reduction, and the Nb powder is 200-325 mesh Nb powder obtained by aluminothermic reduction.

3. The method for preparing a high voltage grade CuCrNb material according to claim 1, characterized in that: In S1, the ball milling time of the ball milling treatment is 300-500 r / min, and the ball mill mixer rotates 360 degrees to perform sufficient mixing for 4-8 hours.

4. The method for preparing a high voltage grade CuCrNb material according to claim 1, characterized in that: In S2, the rubber sleeve is Φ90mm-Φ95mm*1100mm; the length of the electrode rod is 600-800mm, and the diameter is 65-80mm.

5. The method for preparing a high voltage grade CuCrNb material according to claim 1, characterized in that: In S3, the vacuum sintering is specifically as follows: vacuuming for 1.5-3h, and the vacuum reaches 5*10 -3 The pa vacuum sintering furnace is automatically heated, and the heating temperature is 1100-1200℃ for sintering for 28-32h, and the temperature is kept for 4-6h. When the temperature drops to 700-800℃, Ar gas is filled and the fan is turned on for rapid cooling. When the temperature drops below 80℃, the fan is turned off and the furnace is taken out to obtain the electrode rod after vacuum sintering.

6. The method for preparing a high voltage grade CuCrNb material according to claim 1, characterized in that: In S4, The cooling water pressure of the refrigerator is 3-5 bar, the compressed air is 6-8 bar, the He pressure is ≥ 2 bar, and the inlet water temperature is 16-24°C; The smelting current of the smelting is 2-5KA, and the smelting voltage is 15-30V; The cooling water flow rate of the cooling is 200-300 L / min, and the ingot is obtained after cooling for 10-20 minutes.

7. The method for preparing a high voltage grade CuCrNb material according to claim 1, characterized in that: In S7, the annealed forged ingot is placed in a muffle furnace and heated to 850-960°C at room temperature for 1-2 hours, and kept at 850-960°C for 1-2 hours. The forged ingot is then taken out of the furnace and water quenched to obtain a solution treated forged ingot.

8. The method for preparing a high voltage grade CuCrNb material according to claim 1, characterized in that: The temperature of the low-temperature quartz powder is 10-20° C., and the low-temperature quartz powder is continuously stirred by a stirrer; the operating environment temperature is room temperature.

9. The method for preparing a high voltage grade CuCrNb material according to claim 1, characterized in that: The spray is formed by mixing water and reagents, and the concentration of the spray refers to the volume ratio of the reagent to water. The reagent for the first spray treatment is formed by mixing 20-25 g / L of copper sulfate, 3-8 g / L of sodium tartrate and water. The reagent for the second, third and fourth spray treatments is formed by mixing 20-25 g / L of benzotriazole, 30-50 g / L of hydroxymethyl cellulose and water. The spray should be prepared and used immediately.